An Evaluation of the Use of Egg Yolk, Artemia nauplii, Microworms and Moina as Diets in Larval Rearing of Helostoma temmincki Cuvier and Valenciennes - Cheah, C. H.; Sharr, H. A.; Ang, K. J. (1985)
Five day old Helostoma temmincki larvae measing 4.6 ± 0.1 mm in total length were stocked into 12 larval culture tanks at the rate of 1000 larvae/tank (l0 larvae/l). The larvae were fed Diet I (Egg yolk), Diet II (Egg yolk + Artemia naupliz), Diet III (Egg yolk +microworms), and Diet IV (Egg yolk + Moina) for iz period of4 weeks. After 1 week of rearing, larvae fed Diet III measun'ng 8. 4 mm total length and 7.0 mg weight were larger than larvae fed the other diets (P < 0.05). A t the end of two weeks, larvae fed Diets II, III and IV were larger than larvae fed Diet I (P < 0.05). FrOm" week 3 onwards, larvae fed Diet IV were consistently larger (P <0.05). This experiment shows that microworms were very suitable as a starter feed and that Moina was suitable for feeding Helostoma temmincki larvae after week 2 under tropical conditions.